Kanjuruhan Tragedy from A Criminal Law Prespective - Shabrial Aura Putra; Muchamad Iksan (Proceeding International Conference Restructuring and Transforming Law, 2023)
This journal discusses the Kanjuruhan tragedy from the perspective of criminal law. The Kanjuruhan tragedy refers to the events that took place in the Kanjuruhan area, where a number of serious crimes and violations of criminal law have occurred. The purpose of this journal is to analyze the event in criminal law and identify the responsibilities and consequences that may arise. In this journal, the authors use a normative method of analysis to examine various laws and regulations relevant to the Kanjuruhan tragedy. In addition, the author also considers similar cases in criminal law and explains the legal concepts that apply in the context of the Kanjuruhan tragedy. The results of the analysis show that the Kanjuruhan tragedy involved several criminal offenses that violated the law such as murder, vandalism, extortion, and human rights violations. The author identifies several responsible parties, including individuals who committed criminal acts, supervisors who failed to carry out their duties, and a legal system that may have weaknesses.